Experimental study on using waste heat from solar photovoltaic cooling for liquid desiccant regeneration in a solar air-conditioning system - Zulkurnain Hassan (2023)
The utilization of a desiccant cooling system presents a remarkable resolution to address forthcoming energy demand issues, all the while prioritizing human comfort through its ability to effectively control temperature and humidity levels. The typical vapour compression cooling and air conditioning systems may be replaced or supplemented by liquid desiccant cooling systems that are powered by solar photovoltaic (PV) waste heat. This study aims to investigate the utilisation of solar photovoltait cooling waste heat for liquid desiccant regeneration in a solar air conditioning system. The experimental setup incorporates accurate measuring instruments specifically designed to facilitate a wide range of precise observations during the experiment. The performance evaluation of the system was conducted using a regenerator that utilized a desiccant solution consisting of up to 40% concentrated Calcium Chloride (CaCl2). The waste heat from the desiccant, reaching temperatures of up to 60oC, was utilized in a liquid spray towers system for regeneration. The maximum calculated output power for a solar photovoltaic (PV) system with heat recovery was 185.6 W with an efficiency of 26.54%. At 1:00 p.m. the system's maximum temperature was 70oC. The experiment's findings show that the desiccant held in the reservoir can reach a temperature of 65oC. The regenerator modifies the air's specific humidity as the solution's inlet temperature and mass flow rate increase. The rate of water evaporation increases as air flow rates and desiccant solution inlet temperatures increase.